Peningkatan SDM Lokal Dalam Pariwisata Berkelanjutan di Kota Surakarta Jawa Tengah - Wirata, I Nengah; Sumadi , I Gede; Wijayanti, Ni Putu Evi; Darmiati, Made; Liestiandre, Hanugerah Kristiono; Rahmawati; Sarira , Matius Tinna (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2025)
Sustainable tourism is an important aspect in developing the tourism sector, especially for local tourist destinations which require increased human resource (HR) capacity to manage tourism potential independently and competitively. This community service activity aims to improve the skills of local human resources in the Surakarta City Tourism Village in preparing tour packages and digital marketing. Training is carried out through a participatory approach which includes the delivery of theory, practice of preparing tour packages, and digital marketing simulations. The results of the activity showed that participants were able to understand the basic principles of sustainable tourism, develop attractive tour packages, and utilize digital media for promotion. The evaluation also showed an increase in participants' confidence in developing and marketing tourism products independently. Thus, this training has a positive impact on increasing the capacity of local human resources in managing sustainable tourism. It is hoped that the results of this activity can increase the attractiveness of the Surakarta City Tourism Village and become a model for community empowerment in other tourist destinations.